Microstructure and Mechanical Properties of AA6061 Layered Sheet Fabricated by Four-Layer Stack Cold Roll-Bonding - Lee, Seong-Hee (Archives of Metallurgy and Materials, 2026)
Four-layer stack cold roll-bonding (4L-CRB) process is applied to enhance the mechanical properties of AA6061 sheet. Commercial AA6061 sheets having thickness of 1 mm, width 0f 40 mm and length of 300 mm were stacked to four layers, and roll-bonded by two-pass cold rolling. The as roll-bonded Al sheet was then annealed for 1h at temperatures from 200 to 500℃. The conventional rolling (CR) was also proceeded at ambient temperature for AA6061 sheet for comparison. For both CR and 4L-CRB, the as roll-bonded Al sheets showed a typical deformation structure, where the grains are elongated in the rolling direction. However, they exhibited different recrystallization behaviors between the CR and the 4L-CRB. The grain diameter of the specimens annealed at higher temperatures than 350℃ was smaller and more homogeneous in 4L-CRB than in CR. In addition, the mechanical properties of the specimens processed by 4L-CRB were more superior, comparing with those of the CR. The microstructures and mechanical properties of the specimens by 4L-CRB are compared with those by the CR in detail.